Investigating development of pre-service elementary mathematics teachers' pedagogical content knowledge through a school practicum course - AKKOÇ, HATİCE (ELSEVIER SCIENCE BV, 2010)
This study investigates pre-service elementary mathematics teachers' development of pedagogical content knowledge (PCK) through a school practicum course. Four components of PCK were determined and used for the design of the school practicum course. A case study was designed to investigate two pre-service teachers' PCK development with regard to number patterns. Data indicated that observations in real classroom settings and discussions of these observations resulted in considerable improvement in pre-service teachers' PCK especially with regard to the knowledge of student difficulties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Pedagogical content knowledge; number pattern; school practicum course; SECONDARY TEACHERS